2020
DOI: 10.3389/fpsyt.2020.00191
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Resting-State Cerebellar-Cerebral Functional Connectivity in Methamphetamine-Dependent Individuals After Six Months Abstinence

Abstract: Background: Structural and functional alterations in the cerebellum have been consistently reported in addiction literatures. However, evidence implicating the restingstate cerebellar-cerebral functional connectivity in methamphetamine (MA) use disorder still remains limited. Methods: Resting-state functional magnetic resonance imaging (fMRI) scans were obtained from 34 MA dependent individuals with about six months abstinence and 31 healthy controls (well matched for age, gender and education) in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…More importantly, although altered FC correlates with DMN activation in MAs after six months of abstinence, 32 our study confirmed DMN function is impaired in MAs with less than six months of abstinence. Taken together, the alterations in the DMN in short-term MAs may imply disrupted self-awareness and self-related decision-making.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…More importantly, although altered FC correlates with DMN activation in MAs after six months of abstinence, 32 our study confirmed DMN function is impaired in MAs with less than six months of abstinence. Taken together, the alterations in the DMN in short-term MAs may imply disrupted self-awareness and self-related decision-making.…”
Section: Discussionsupporting
confidence: 69%
“…After six months of abstinence, MAs exhibited disrupted FC between the cerebellum and DMN. 32 Our findings further demonstrated decreased DMN-CN FC in short-term MAs, implying that impaired DMN-CN connectivity is characteristic of marked damage.…”
Section: Discussionsupporting
confidence: 69%
“…McKetin et al (2008) observed that methamphetamine is sometimes mixed with other drugs and sold as "ecstasy. Li X et al (2020) held that methamphetamine-dependent individuals show disrupted functional connectivity between the cerebellum and several cerebral functional networks compared to healthy controls, including default mode, affective-limbic, and sensorimotor networks. It also has socio-economic and legal consequences (Barman-Adhikari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, differences in neural function can be identified by measuring the connectivity from the BOLD time series between the various regions of the brain. By using rs-fMRI data, previous studies examined the effects of MA on the functional connectivity (FC) of the brain and discovered significant differences that may be related to some of the core symptoms observed in MA addicts (Kohno et al, 2014 ; Dean et al, 2015 ; Zhang et al, 2018 ; Li et al, 2020 ). Although these findings provide new insights into the neural features of MA addiction, the great majority of these research are based on explanatory models and the generalizability of the results remains unclear.…”
Section: Introductionmentioning
confidence: 99%